IMPLIKASI TERHADAP OPINI AUDIT GOING CONCERN: FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA EMITEN MANUFAKTUR DI INDONESIA - Saifudin Saifudin; Aprih Santoso; Ardiani Ika Sulistyawati; Rahmanda Hasna Putri (Universitas Dian Nuswantoro, 2023)
This study aims to test and prove the effect of Audit Quality, Debt Ratio, Company Size, Audit Lag on Going Concern Audit Opinion in manufacturing companies that have been listed on the Indonesia Stock Exchange from 2017 to 2021. The financial statements tested are financial statements that have been through the auditing process by the Public Accounting Firm and the financial statements ending on 31 December. The research data was collected using the purposive sampling method by downloading data through the official IDX website. This study uses logistic regression analysis techniques. The results showed that the independent variables Debt Ratio and Audit Lag had a positive effect on Going Concern Audit Opinion. while the independent variables Audit Quality and Company Size do not have a positive effect on Going Concern Audit Opinion.